Analysis of Public Relations Strategy in Improving Islamic Education Quality Management in the Digital Era: Concept and Implementation - Iik Timamah; Faridatul Jannah; Faiqotul Munawwarah; Khorina Badriyah; Ali Nurhadi (al-Afkar, Journal For Islamic Studies, 2025)
This article aims to analyze public relations strategies in improving the quality management of Islamic education in the digital era. This study uses a qualitative method with a conceptual approach model that focuses on examining theoretical concepts. The results of the analysis show that public relations strategies play a crucial role in improving the quality of Islamic education in the digital era through effective communication with various stakeholders. Using social media as a communication and marketing medium allows for fast and efficient dissemination of information, and helps build positive relationships with the community and strengthen the reputation of Islamic educational institutions. With effective resource management. The right communication strategy, public relations can attract public support, ensure the sustainability of the institution, and achieve the goal of quality Islamic education.